CompTIA PenTest+ Certification All-In-One Exam Guide, Second Edition (Exam PT0-002) - Linn, Heather; Nutting, Ray (McGraw-Hill Education, 2022)
This fully-updated guide delivers complete coverage of every topic on the current version of the CompTIA PenTest+ certification exam. Get complete coverage of all the objectives included on the CompTIA PenTest+ certification exam PT0-002 from this comprehensive resource. Written by expert penetration testers, the book provides learning objectives at the beginning of each chapter, hands-on exercises, exam tips, and practice questions with in-depth explanations. Designed to help you pass the exam with ease, this definitive volume also serves as an essential on-the-job reference. Covers all exam topics, including: Planning and engagement Information gathering Vulnerability scanning Network-based attacks Wireless and radio frequency attacks Web and database attacks Cloud attacks Specialized and fragile systems Social Engineering and physical attacks Post-exploitation tools and techniques Post-engagement activities Tools and code analysis And more Online content includes: 170 practice exam questions Interactive performance-based questions Test engine that provides full-length practice exams or customizable quizzes by chapter or exam objective.